Genotyping of Mycobacterium tuberculosis by spoligotyping in the area of The Office of Disease Prevention and Control Region 12, Songkhla - Jekloh, Nasron; Mukem, Daris; Hemmhud, Tonseal; Salaeh, Nurulsahidah; Phetsuksiri, Benjawan; Singthong, Seri (Disease Control Journal, 2021)
Tuberculosis (TB) remains an deadly infectious disease causing a serious public health problem in many parts of the world as well as in Thailand caused by Mycobacterium tuberculosis complex (MTC) in which less genotypic diversity data available in Thailand. Genotypic differentiate method is an epidemiological tool (epidemiological investigation and tracking of TB transmission) to differentiate local strains and allow the comparison of strains with global isolates. This study manipulated spoligotyping and aimed to investigate strains circulating in 8 provinces: Songkhla, Yala, Pattani, Narathiwat, Trang, Songklha, Satun and Phatthalung under The Office of Disease Prevention and Control Region 12. A total of 138 MTC isolates collected from pulmonary tuberculosis patients were genotyped by spoligotyping, and the strains were compared with those in the international spoligotype database (SpolDB4). Altogether 15 different spoligotype patterns were identified, and 37 strains were found as new genotype patterns. The East African-Indian (EAI) groups were the most frequent strains investigated followed by Beijing, 36.23% (50/138) and 32.61% (45/138), respectively. Among EAI groups EAI5 were the most commonly investigated followed by EAI6_BGD1 (Bangladesh) and EAI 2_NTB (Nonthaburi), 36.00% (18/50), 30.00% (15/50) and 18.00% (9/50) respectively. This standard and practical spoligotyping is able to identify the diversity of MTC strains circulating in this region.